(untitled) (Revista Espacio Regional, 2020)
In this article are analyzed facts verified by scientific research in the period from 1996 to 2016, about the environmental, health and socioeconomic impacts of Genetically Modifies Organisms (GMOs) crops. Considering the recent history and the seriousness of these risks, it should consider the need to take measures to avoid his situation that benefits a few companies and harms most of the population of American countries, it is prolonged in time.